Evaluating Mechanical Circulatory Support Devices in Cardiogenic Shock: A Systematic Review of Randomized Controlled Trials - Nunkoo, Sarvesh; Robinson, Jared; Banerjee, Indrajit (Journal of Advances in Internal Medicine, 2025)
Cardiogenic shock is a severe medical condition that bears a high morbidity and mortality. It is most commonly precipitated by myocardial infarctions, which impair the heart's ability to effectively act as a pump and provide perfusion to the body's vital organs. Pathophysiologically, cardiogenic shock is characterized by the heart's inability to maintain its cardiac output (CO), resulting in a compromise of perfusion to the vascular beds. Mechanical circulatory assist devices are at the higher end of the spectrum in terms of treatment modalities for Cardiogenic shock and are both costly and require significant skill and training to operate. This systematic review of randomized control trials aims to delineate between the feasibility and efficacy of the most commonly implemented mechanical heart assist devices, comparing intra-aortic balloon pump devices and ventricular assist devices. A thorough search was conducted using PubMed, Trip database (Turning Research into Practice) and Cochrane Central Register of Controlled Trials (CENTRAL) to identify the relevant manuscripts. A combination of keywords and Boolean operators was used for the data extraction (((percutaneous coronary intervention [Title/Abstract]) OR (impella pump[Title/Abstract])) AND (cardiogenic shock [Title/Abstract])) OR (intra aortic balloon pump [Title/Abstract]). The literature search generated a total of 5656 articles. Non-RCTs, cohort studies, cross-sectional studies, case control studies, case series, case reports, in vitro studies, animal experiments, commentaries, letters to the editor and expert opinions were additionally excluded. Four RCTs were finally assessed regarding the Mechanical circulatory support devices in cardiogenic shock and hence included in the systematic review for quality synthesis. Intra-aortic balloon pump insertion in combination with inotropic support is suggested as a first line intervention for myocardial infarctions complicated by cardiogenic shock, whereas ventricular assist devices with the capability of percutaneous insertion such as “Impella” are proven more useful in patients with triple vessel disease undergoing percutaneous coronary intervention. The selection of which mechanical support device to use in a particular patient is therefore of the utmost importance as the correct device should be selected for the specific underlying pathology in order to improve the patient and outcome and minimize the associated complications therewith.